Propaganda Tiongkok di Tengah Perang Dagang dengan Amerika Serikat - Putri, Nafisyah Viona (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2024)
The tension between China and the United States regarding economics led to a trade war. This action was exacerbated by mutual boycotts, negatively impacting both the US and China. Additionally, there has been a dissemination of propaganda, particularly from China. As a communist country, it is interesting to observe how China spreads propaganda throughout its territory. Utilizing its power and existing media, China seeks to campaign propaganda about this trade war as effectively as possible. Furthermore, the effectiveness of this propaganda can be seen in relation to the intended goals and the response of the audience, which consists of the Chinese population itself.